Analysis of Engine and Propeller Selection for Unmanned Aircraft LSU-05 NG - Novita Atmasari; Muksin Muksin; Hartono Hartono; Ryan Hidayat (Institut Teknologi Dirgantara Adisutjipto, 2020)
This research focuses on analyzing the selection of engine and propeller for the propulsion system of LSU-05 NG by calculating the aircraft power needs. The aircraft power is evaluated in two loading conditions, namely heavy loading with regard to minimum take-off speed and light loading with regard to maximum cruise speed. Furthermore, from the five engine recommendations available, propeller rotation efficiency, thrust generated, and engine weight that meets the aircraft DRO (Design Requirment and Objective) are analyzed. The results of this research provide recommendations for using an engine with a minimum power of 16.5 hp with the main candidate is DLE 170 and a 32x10 size propeller as the LSU-05 NG propulsion system.